Serbian Cyrillic – Expression of the Serbian spiritual being - Janjić, Jovan (Napredak, 2023)
The alphabet is an integral part of a nation’s culture. The nation creates or accepts it, forming it by its own standards; thus, it is an expression of the spiritual being of the nation creating or accepting it. The Serbian nation has the culture that is more than one millennium old, created on its language and alphabet, mostly and for the longest period of time solely in the Cyrillic. In that manner, the Cyrillic has marked both the spiritual and the national being of Serbia – it has become an integral part of the Serbian nation’s identity. The nation and the alphabet stand in a relationship of interaction both in the creation of the alphabet and in the building and preservation of the national identity.
Keywords: alphabet; Cyrillic; language; Serbian nation; identity